“Where wasteful Time debateth with Decay”: Shakespeare sonnets in I.Ο. Shaytanov’s interpretation - E. M. Lutsenko (Шаги, 2024)
A review of: Shaytanov, I.O. (Ed.) (2022). Shekspir U. Sonety [Shakespeare, W. Sonnets]. Aleteiia. (In Russian).